Peran Pemerintah dan Kader Masyarakat dalam Pemberdayaan Masyarakat untuk Pengolahan Sampah - Mohammad Erdi Ferdiansyah; Arsiyah Arsiyah (Universitas Muhammadiyah Sidoarjo, 2014)
The purpose of this study to describe and analyze the role of government and Sumringah Ngampelsari interests group on waste management basedempowerment in the Ngampelsari village. This study used qualitative approach. The results of this study indicated that the processing and utilization of organic waste is done by simple composting technology. In order to maximize the results of processing waste become compost, the community maintain ornamental plants and medicinal plants. While, inorganic waste to be processed into valuable goods. Waste management based on empowerment is provided by guidance about awareness to the citizens to cultivate their waste and used compost to plantornamental plants, traditional plants and provided of bins in their neighborhood.